The sanctuary at Keros in the Aegean Early Bronze Age: from centre of congregation to centre of power - Renfrew, Colin; Boyd, Michael J.; Athanasoulis, Demetris; Brodie, Neil; Carter, Tristan; Dellaporta, Katerina; Floquet, Marie; Gavalas, Giorgos; Georgakopoulou, Myrto; Gkouma, Myrsini; Hilditch, Jill; Krijnen, Ayla; et al. (Journal of Greek Archaeology, 2022)
This article aims to summarise the results of three periods of fieldwork carried out since 2006. These are the Cambridge Keros Project of 2006–2008, the Keros Island Survey of 2012–2013, and the Keros-Naxos Seaways Project of 2015–2018. Taken together, these form a coherent, large-scale project that aimed to study a maritime landscape in some depth, putting the Kavos and Dhaskalio sites in a broader context, while through excavation understanding in great detail the formation, use and abandonment of the sanctuary site on Kavos and the large built-up area on Dhaskalio.